1995
DOI: 10.1088/0954-3899/21/6/002
|View full text |Cite
|
Sign up to set email alerts
|

Alpha+28Si cluster structure as solitons on the nuclear surface

Abstract: The characteristic alpha-particle spectra from the decay of intermediate states in α+ 28 Si (32 S) to the silicon ground state have been measured during the bombardment of thick targets. The α-spectra were measured in backward angles for the determination of the spins of the states formed in elastic alpha scattering. The level spectra have been investigated in terms of a nonlinear Lagrangean which gives a quantum analogue to the classical large amplitude collective motion in nuclei, succesfully used for the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…We have shown that by assuming a travelling wave profile this equation becomes a MKdV equation which, by a nonlinear Miura transformation, yields finally a KdV equation. Consequently, a full correspondence with the previous classical description is obtained [26]. The quantum fluctuations around the classical solutions (i.e.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…We have shown that by assuming a travelling wave profile this equation becomes a MKdV equation which, by a nonlinear Miura transformation, yields finally a KdV equation. Consequently, a full correspondence with the previous classical description is obtained [26]. The quantum fluctuations around the classical solutions (i.e.…”
Section: Introductionsupporting
confidence: 62%
“…In this way we introduced a new coexistence model consisting of the usual shell model and a cluster-like model describing a soliton moving on the nuclear surface. This model has already been shown to excellently describe the experimental preformation factors for or and cluster [26] decays. A similar model was introduced microscopically in [U] and, earlier, by Konnecke etol [30].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…-A soliton approach is, indeed, the only description so far that can give a suffiently large number of states [20]. It has, however, problems with a physical interpretation because of the non-linear approach and because of the excitation of the soliton ("orbiting alpha particle") itself.…”
Section: -Discussion and Outlookmentioning
confidence: 99%
“…3 Other notable features of the theory include its description of solitons and breather modes, features in quantum optics, 4 molecular and solid state physics phenomena, 5 and solitons in nuclear and particle physics. 6 In contrast with linear theories which exhibit smooth regular motion, nonlinear models require nonlinear partial differential equations (NPDE) and show strong couplings between different mechanisms and parts of the system. Also, the nonlinear interactions involve multiple scales 7 and are related with self-similar patterns or fractals.…”
Section: Introductionmentioning
confidence: 99%